2011
DOI: 10.1089/ten.teb.2010.0704
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolds Based Bone Tissue Engineering: The Role of Chitosan

Abstract: As life expectancy increases, malfunction or loss of tissue caused by injury or disease leads to reduced quality of life in many patients at significant socioeconomic cost. Even though major progress has been made in the field of bone tissue engineering, present therapies, such as bone grafts, still have limitations. Current research on biodegradable polymers is emerging, combining these structures with osteogenic cells, as an alternative to autologous bone grafts. Different types of biodegradable materials ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
226
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(238 citation statements)
references
References 257 publications
(366 reference statements)
3
226
1
8
Order By: Relevance
“…The high occurrence of these conditions are evidence by more than 2.2 million bone graft used in orthopaedic annually worldwide [1]. Bone grafts are used to augments or stimulates the formation of new bone, in cases such as the healing of the skeletal fractures, or between bones across a diseased joint; to replace and regenerate lost bone as a result of trauma, infection, or disease or to improve bone healing response and regeneration of tissues around surgical implanted devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high occurrence of these conditions are evidence by more than 2.2 million bone graft used in orthopaedic annually worldwide [1]. Bone grafts are used to augments or stimulates the formation of new bone, in cases such as the healing of the skeletal fractures, or between bones across a diseased joint; to replace and regenerate lost bone as a result of trauma, infection, or disease or to improve bone healing response and regeneration of tissues around surgical implanted devices.…”
Section: Introductionmentioning
confidence: 99%
“…The tissue regeneration of these bone graft is measured in terms of their osteogenic, osteoconductive and osteoinductive potential [2]. Autografts are considered the gold standard for bone repair; however, such as bone donor site morbidity ( [1,3]). Another alternative is the allograft, which is bone tissue from cadaver or living donors, eliminates donor site morbidity, but has the potential risk of adverse immunological response and also lacks osteogenic capacity of autograft [4].…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of chitosan depends on the free amino and N-acetyl groups, which are soluble in acidic pH 18) . Chitosan, used in this study, presents a wide range of properties that make it appropriate for tissue engineering applications because of its biodegradability, biocompatibility, antibacterial activity, wound healing properties, and bioadhesive character 9) . One of the most important characteristic of chitosan, for tissue engineering applications, is its ability to be shaped into various form, such as microspheres, paste, membranes, sponges, fibers and porous scaffolds 19) .…”
Section: Discussionmentioning
confidence: 99%
“…To accomplish the goals of tissue engineering, scaffolds should satisfy the following requirements; should be porous to allow placement of cells and growth factors, should allow effective transport of nutrients, oxygen, and waste, should be biodegradable, leaving no toxic byproducts, should be replaced by regenerative tissue while retaining the shape and form of the final tissue structure, should be biocompatible and should have adequate physical and mechanical strength 8) . In recent studies, naturally derived polymers have been proposed for the scaffold such as starch, gellan gum, soy, silk and chitosan 9) . In particular, chitosan has shown an excellent combination of properties and it has been demonstrated that it is suitable biomaterial for the development of scaffolds for bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation